PENINGKATAN KESADARAN MASYARAKAT PENTINGNYA PENDIDIKAN, MELAUI SOSIALISASI DI PUSAT KEGIATAN BELAJAR MASYARAKAT - Siti Tarwiah; Athaya Syahla Maharani; Rahmi Hidayati; Jakiya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is a fundamental right for every citizen of Indonesia as mandated by the 1945 Constitution. However, equitable access to education in Indonesia still faces various challenges. Social, economic, and geographical disparities have caused parts of the community to remain underserved and unable to obtain proper educational services. As an alternative solution, non-formal education is provided through Community Learning Centers (PKBM), which function to ensure lifelong learning opportunities for society. Nevertheless, the low level of public understanding and participation regarding the role of PKBM becomes an obstacle to optimizing its function. This community service program aims to increase public awareness and understanding of the importance of non-formal education through socialization activities at PKBM Insan Mandiri Gemilang in Tangerang City. The implementation method used a participatory approach through lectures, interactive discussions, and question-and-answer sessions involving the community and local community leaders. The results of the activity indicate a significant improvement in community understanding regarding the role of PKBM as a flexible alternative educational institution that is relevant to societal needs. The community also demonstrated positive attitudes and growing interest in participating in programs offered by PKBM. This activity proves that well-conducted socialization efforts can increase awareness of lifelong education and strengthen the position of PKBM as a community empowerment platform in the digital era.